The factors influenced career choices among bachelor’s degree final year students of UiTM Sarawak Campus Samarahan / Fatin Nabilah Abdul Rahim and Nur Aqma Syairah Syafiqah Md Zaidi - Abdul Rahim, Fatin Nabilah; Md Zaidi, Nur Aqma Syairah Syafiqah (2018)
This chapter will provide a review of literature on the factors influence of career choice among Bachelor’s Degree final year students of UiTM Sarawak Campus Samarahan and also the conceptual framework. Section 2.1 will discuss on the career choice among students. Section 2.2 will elaborate on factors influencing career choice among students. Section 2.3 mentions about gender differences in career choice and 2.4 will discuss on the conceptual framework. Section 2.5 will discuss on hypotheses of the study. Lastly, Section 2.6 will explain about this chapter summary.